(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Susila IW, Sumiartha IK, Supartha IW, Yudha IKW, Utama IWEK, Yasa IWS, Wiradana PA. 2022. Abundance, distribution mapping and DNA barcoding of Procontarinia robusta (Diptera: Cecidomyiidae), a mango gall midge in Bali, Indonesia. Biodiversitas 23: 6428-6436. Gall midge (Procontarinia robusta) is an important pest of mango plants in various countries in the world, including Indonesia. This pest causes very serious damage to mango leaves which until now has not been reported. This study aims to map the distribution and abundance of the pest population and identify the pest species using the DNA barcode method on mango tree plantations in Bali, Indonesia. The survey method was used to collect data from various districts and cities in Bali Province, Indonesia. Mitochondrial COI primers were used to identify DNA barcodes. The results showed that the highest population abundance of P. robusta was found in Denpasar City. These pests have spread evenly throughout the Province of Bali, from the lowlands to the middle and highlands. Through a molecular approach, the insect pest that causes mango leaf gall in Bali Province is identified as P. robusta as the first report that can be used by researchers, related agencies, and farmers to be alert and ready with strategies and control tactics in the future. Further research is needed related to monitoring using sex pheromones or plant volatiles and the search for natural enemies for monitoring purposes and initiation towards biological control.